2011
DOI: 10.4314/sljbr.v3i1.66653
|View full text |Cite
|
Sign up to set email alerts
|

Blindness Caused by Pterygium – A Case Report

Abstract: Pterygium leading to bilateral blindness and forcing patient to quit job is uncommon. This is a case report of a 46 year old indigent woman who had blinding pterygia over 10 years. She could not afford pterygium excision offered in a private eye clinic where she initially presented after a period of unsuccessful self medication. She was forced out of sewing job consequent to her inability to thread needle, difficulty reading number on the tape rule and difficulty recognising faces of her clients. Six years lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…[ 2 20 ] Evidence has shown that most cases of pterygium result in with the rule astigmatism as shown in our study and other similar studies. [ 7 11 ] Our study demonstrated improvement in visual acuity and reduction in induced astigmatism after pterygium excision. These findings were found to be statistically significant.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…[ 2 20 ] Evidence has shown that most cases of pterygium result in with the rule astigmatism as shown in our study and other similar studies. [ 7 11 ] Our study demonstrated improvement in visual acuity and reduction in induced astigmatism after pterygium excision. These findings were found to be statistically significant.…”
Section: Discussionmentioning
confidence: 67%
“…These include the bare sclera, excision with conjunctival autografting or amniotic membrane transplantation and beta irradiation. [ 2 6 7 ] Conservative treatment could be adopted for temporary relief of symptoms such as the use artificial tears or lubricants and topical anti-inflammatory agents. [ 6 ] The effect of pterygium on corneal refractive status may be measured by refraction, keratometry, corneal topography, and computerized video-keratoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the molecular progression of pterygia in untreated patients, covering several years, is unknown and awaited. Only one report includes a bilateral pterygium patient that received medical intervention after 10 years [ 129 ]. Unfortunately, molecular characterization of the biopsy is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It can be unipolar usually nasal or temporal and frequently results in visual disturbance. [28] Visual disturbance occurs when the pterygium indents the cornea or crosses the pupillary axis. In a study in south India, 9.5% of subjects had pterygium which was more common in females and in rural dwellers.…”
Section: Discussionmentioning
confidence: 99%